Additive manufacturing in unmanned aerial vehicles (UAVs): Challenges and potential - Goh, G. D. (2018)
Unmanned aerial vehicles (UAV) are gaining popularity due to their application in military, private and public sector, especially being attractive for fields where human operator is not required. Light-weight UAVs are more desirable as they have better performance in terms of shorter take-off range and longer flight endurance. However, light weight structures with complex inner features are hard to fabricate using conventional manufacturing methods. The ability to print complex inner structures directly without the need of a mould gives additive manufacturing (AM) an edge over conventional manufacturing. Recent development in composite and multi-material printing opens up new possibilities of printing lightweight structures and novel platforms like flapping wings with ease. This paper explores the impact of additive manufacturing on aerodynamics, structures and materials used for UAVs. The review will discuss state-of-the-art AM technologies for UAVs through innovations in materials and structures and their advantages and limitations. The role of additive manufacturing to improve the performance of UAVs through smart material actuators and multi-functional structures will also be discussed.